Ame Construction Sdn Bhd / Muhamad Imran Zaidon - Zaidon, Muhamad Imran (UiTM Cawangan Johor Kampus Pasir Gudang, 2021)
Industrial Training is a compulsory requirement for student in certain programs at all level of higher education in Institution of Higher Learning . To increase the level of graduate able to work , industrial training program was introduced to strength the competencies required. I was having my industrial program at AME CONSTRUCTION SDN BHD , located at I-Park Senai and being placed at Port of Tanjung Pelepas. The duration for this internship is about more than eighteen weeks started from 12 October 2020 till 10 February 2021. Here in this training , I'm being assign under Quality Control Department , under supervision of my supervisor , En Ahmed Redzuan Bin Razali , Senior QAQC Engineer . Here in this department, I'm being trained to prepared required document for every work and joined the inspection for every structure with consultant agencies. For this industrial training, I've gained so much experience and have been exposed to variety of actual site condition , compared to what I've learn theoretically before. I've learn to inspect the rebar and formwork of every structure , type of machines that been used to concrete work, how to overcome some discrepancy and so on. Industrial training refers to exposed student to real life experiences of the engineering of work and to get involved in civil engineering project before graduation After experience by myself, I realizes that there still a lot of things I need to remastered in order to not only be a good engineer , but also good at making decision in every problem. Last but not least , I hope this program should be continue as the student will get more knowledge on what they studied for this six semester. Life is tough , so we have to be tougher